Lithium adsorption material and preparation method and application thereof

By using polyvinyl chloride, polyacrylic acid framework and hydroxyl-modified lithium-ion sieve in lithium adsorbents, lithium adsorbents with specific pore structures are prepared, which solves the problem of poor hydrophilicity and stability of lithium adsorbents and improves adsorption Capacity and cycling performance achieve efficient lithium ion adsorption and desorption.

CN119186513AActive Publication Date: 2024-12-27CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202410851791.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-27
Filing Date
2024-06-27
Publication Date
2024-12-27
Estimated Expiration
2044-06-27

AI Technical Summary

Technical Problem

The existing lithium adsorbents have poor hydrophilicity and poor stability during the granulation process, resulting in the prone to agglomeration of lithium ion sieves, blockage of pores and rupture, affecting the adsorption capacity and circulation performance.

Method used

Using polyvinyl chloride and polyacrylic acid as the skeleton, the mixed liquid droplets are added to the aqueous solvent under specific temperature and humidity conditions to prepare lithium adsorption materials with specific pore structures, including small outer shell holes and internal cores. The large pore structure increases the mass transfer rate of water and salt, and is connected to the skeleton through a hydroxyl-modified lithium ion sieve, thereby improving the adsorption and desorption rate of lithium ions.

Benefits of technology

It significantly improves the adsorption capacity of lithium, extends the recycling service life of the material, improves mechanical properties and swelling resistance, avoids the embedding and aggregation of lithium ion sieves, and enhances the stability and adsorption efficiency of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186513A_ABST
    Figure CN119186513A_ABST
Patent Text Reader

Abstract

The invention relates to the field of adsorption materials, and discloses a lithium adsorption material and a preparation method and application thereof. The lithium adsorption material comprises a core body and a shell layer coating the surface of the core body, holes are formed in the shell layer of the lithium adsorption material, and the average diameter of the holes measured by an SEM (scanning electron microscope) is 0.01-2.5 microns; the core body of the lithium adsorption material comprises finger-shaped holes, and the longest average length of the finger-shaped holes, measured by an SEM (scanning electron microscope), of the section of the lithium adsorption material is 1-7 microns; the shortest average length is 0.05 to 2.5 [mu] m; and the thickness of the shell layer of the lithium adsorption material, which is measured by an SEM (scanning electron microscope), is 1-550 [mu] m. The lithium adsorption material with the specific structure is of a special structure with small outer shell layer holes and large inner core body holes, the mass transfer rate of water and salt can be increased, and when the lithium adsorption material is used for extracting lithium in a liquid environment, the lithium adsorption capacity can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of adsorption materials, and in particular to a lithium ion adsorption material and a preparation method and application thereof. Background Art

[0002] With the rapid development of the lithium battery industry, the demand for lithium resources in various industries is continuing to grow, and the importance of lithium production is also increasing. At present, lithium resources are mainly distributed in lithium ore and salt lake brine, but lithium ore resources are constantly decreasing and the development cost is increasing; in contrast, the lithium water resources in salt lake brine are low in cost and rich in reserves. my country has abundant liquid lithium resources, but extracting lithium from lithium water resources is a challenging task.

[0003] At present, the main methods for extracting lithium from salt lakes include adsorption, precipitation, extraction, electrodialysis, calcination, etc. Among them, the adsorption method has the advantages of simple process, green energy saving, and good selectivity. It is superior to other methods in terms of time and cost, and has broad application prospects. Since salt lake brine often has the problem of low lithium quality, the core of lithium extraction by adsorption is to prepare highly selective adsorbents. Highly selective lithium adsorbents mainly include ion sieve adsorbents and amorphous hydroxide adsorbents. However, since these adsorbents are in powder form after synthesis, they cannot be directly used in conventional equipment such as fixed beds for adsorption-desorption lithium extraction. Currently, lithium adsorbents are also granulated to obtain granular lithium adsorbent materials. Common granulation methods are: (1) using inorganic binders such as alumina, silica gel, etc. for granulation. The granular adsorbent prepared by this method is simple, but has poor stability and often needs to be used together with a polymer granulation method; (2) using natural polymer materials such as chitosan, sodium alginate, etc. for granulation, but the long-term performance stability of the product prepared by this method is poor; (3) using organic polymer materials such as PU, PAM, PVC as a binder for granulation, but the prepared granular adsorbent has poor hydrophilicity and is easy to cause the embedding of the powder adsorbent, which greatly reduces the adsorption capacity and has poor long-term cycle performance.

[0004] Based on the above background, there is an urgent need to solve the problems of poor hydrophilicity of PVC-based granulation products, adsorbent embedding and decreased long-term cycle performance. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems in the prior art that granulated products with polyvinyl chloride as the skeleton have poor hydrophilicity, poor wrapping stability for lithium ion sieves, and the lithium ion sieves are easy to agglomerate, and then the pores of the adsorbent are blocked and broken due to salt crystallization during the recycling process. A lithium adsorption material and a preparation method and application thereof are provided. The lithium adsorption material comprises a core body with a specific pore structure and surface pores with a specific average diameter coated on the surface of the core body, and the shell layer has a specific thickness. The lithium adsorption material with the above-mentioned specific structure presents a special structure with small outer shell pores and large inner core pores, which can increase the mass transfer rate of water and salt. When it is used for lithium extraction in a liquid environment, the adsorption capacity of lithium can be significantly improved.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a lithium adsorption material, wherein the lithium adsorption material comprises a core body and a shell layer coated on the surface of the core body;

[0007] There are pores on the shell layer of the lithium adsorption material, and the average diameter of the pores measured by SEM electron microscopy is 0.01-2.5 μm;

[0008] The core of the lithium adsorption material contains finger-shaped pores, and the longest average length of the finger-shaped pores measured by SEM electron microscopy on the cross section of the lithium adsorption material is 1-7 μm, and the shortest average length is 0.05-2.5 μm;

[0009] The shortest average length of the finger-like holes in the core is greater than the average diameter of the holes in the shell;

[0010] The thickness of the shell layer of the lithium adsorption material measured by SEM electron microscope is 1-550 μm.

[0011] A second aspect of the present invention provides a method for preparing a lithium adsorption material, the method comprising the following steps:

[0012] (1) mixing polyvinyl chloride, polyacrylic acid, lithium ion sieve and oil phase solvent to obtain a mixed solution;

[0013] (2) Under the conditions of temperature of 20-60° C. and humidity of 40-80%, the mixed solution is added dropwise to an aqueous solvent to obtain a lithium adsorption material.

[0014] The third aspect of the present invention provides a lithium adsorption material prepared by the above method.

[0015] A fourth aspect of the present invention provides an application of a lithium adsorption material in lithium extraction.

[0016] Through the above technical solution, the lithium adsorption material and its preparation method and application provided by the present invention achieve the following beneficial effects:

[0017] The lithium adsorption material provided by the present invention comprises a core with a specific pore structure and pores with a specific average diameter coated on the surface of the core, and the shell has a specific thickness. The lithium adsorption material with the above-mentioned specific structure presents a special structure with small pores in the outer shell and large pores in the inner core, which can increase the mass transfer rate of water. When it is used for lithium extraction in a liquid environment, it can significantly improve the adsorption capacity of lithium.

[0018] Furthermore, the lithium adsorption material includes a skeleton and a hydroxyl-modified lithium ion sieve dispersed in the skeleton, and the skeleton includes polyvinyl chloride (PVC) and polyacrylic acid, and the lithium ion sieve is connected to the skeleton through a hydroxyl group. Among them, the hydroxyl group in the lithium ion sieve has good compatibility with the polar group (-COOH) on the polyacrylic acid molecular chain and polyvinyl chloride, which can make the lithium ion sieve evenly dispersed in the skeleton containing polyvinyl chloride and polyacrylic acid, reduce the embedding phenomenon of the adsorbent (lithium ion sieve), and at the same time, the carboxyl group (-COOH) on the polyacrylic acid molecular chain can promote lithium ion transfer, thereby significantly improving the adsorption rate of the lithium adsorption material.

[0019] Furthermore, polyacrylic acid can inhibit the formation of salt crystals, especially the formation of salt crystals under high salt conditions, thereby reducing the phenomenon of pore blockage of the lithium adsorption material due to the formation of inorganic salt crystals in the internal pores of the lithium adsorption material during the cyclic adsorption and desorption process, thereby improving the desorption efficiency of lithium ions and avoiding the phenomenon of polyvinyl chloride rupture caused by the exchange of water flow and salt during long-term use, thereby extending the recycling period of the lithium adsorption material.

[0020] Furthermore, polyacrylic acid has excellent hydrophilicity and mechanical strength, and can significantly improve the mechanical properties of the skeleton containing polyacrylic acid and the swelling properties in a salt solution.

[0021] In the method for preparing lithium adsorption material provided in the present invention, under specific temperature and humidity conditions, a mixed solution containing polyvinyl chloride, polyacrylic acid and lithium ion sieve is added dropwise to an aqueous solvent, and the obtained lithium adsorption material is a core having a specific pore structure and a surface pore structure with a specific average diameter coated on the surface of the core, and the shell layer has a specific thickness. The lithium adsorption material having the above-mentioned specific structure presents a special structure with small pores in the outer shell layer and large pores in the inner core body, which can increase the mass transfer rate of water and salt, and when it is used to extract lithium in a liquid environment, it can significantly improve the adsorption capacity of lithium. In addition, polyacrylic acid has excellent hydrophilicity and mechanical strength, which can significantly improve the mechanical properties of the skeleton containing polyacrylic acid and the swelling properties in salt solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a SEM electron microscope photograph of the surface of the lithium adsorption material prepared in Example 1;

[0023] Figure 2 is a SEM electron microscope photograph of a cross section of the lithium adsorption material prepared in Example 1;

[0024] Figure 3 is a SEM electron microscope image of a cross section of the lithium adsorption material prepared in Example 1;

[0025] Figure 4 This is a SEM electron microscope image of a cross section of the lithium adsorption material of Comparative Example 1;

[0026] Figure 5 This is a SEM electron microscope image of a cross section of the lithium adsorption material of Comparative Example 2;

[0027] Figure 6 is a SEM electron microscope picture of the cross section of the lithium adsorption material of Example 1 after being used 30 times in the adsorption column;

[0028] Figure 7 This is a SEM electron microscope picture of the cross section of the lithium adsorption material adsorption column of Comparative Example 1 after being used 30 times.

[0029] Figure 8 is a photograph of the lithium adsorption material prepared in Example 1. DETAILED DESCRIPTION

[0030] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0031] A first aspect of the present invention provides a lithium adsorption material, the lithium adsorption material comprising a core body and a shell layer coated on the surface of the core body;

[0032] There are pores on the shell layer of the lithium adsorption material, and the average diameter of the pores measured by SEM electron microscopy is 0.01-2.5 μm;

[0033] The core of the lithium adsorption material contains finger-shaped pores, and the longest average length of the finger-shaped pores measured by SEM electron microscopy on the cross section of the lithium adsorption material is 1-7 μm, and the shortest average length is 0.05-2.5 μm;

[0034] The shortest average length of the finger-like holes in the core is greater than the average diameter of the holes in the shell;

[0035] The thickness of the shell layer of the lithium adsorption material measured by SEM electron microscope is 1-550 μm.

[0036] In the present invention, the lithium adsorption material comprises a core having a specific pore structure and pores having a specific average diameter coated on the surface of the core, and the shell has a specific thickness. The lithium adsorption material having the above-mentioned specific structure presents a special structure with small pores in the outer shell and large pores in the inner core, which can increase the mass transfer rate of water. When it is used for lithium extraction in a liquid environment, it can significantly improve the adsorption capacity of lithium without leaking the powdered lithium ion sieve.

[0037] In the present invention, the lithium adsorption material is sectioned at a spacing of 0.5 mm along the direction parallel to the equator of the particles of the lithium adsorption material and the direction perpendicular to the equator of the particles of the lithium adsorption material to observe the core structure of lithium ion adsorption in different sections. Through observation, it can be found that in different sections, the core of the lithium adsorption material contains finger-like holes, and the longest average length of the finger-like holes measured by the SEM electron microscope in each section meets 1-7μm; the shortest average length meets 0.05-2.5μm. Based on this, the inventor of the present application reasonably expects that the core of the entire lithium adsorption material contains finger-like holes, and the finger-like holes are three-dimensional structures and have the specific structure described in the present invention.

[0038] In the present invention, when the longest average length and the shortest average length of the finger-like holes in the core of the lithium adsorption material are tested by using a SEM electron microscope, 10 observation points are randomly selected for SEM testing, each observation area is not less than 500×500 μm, and the average value is calculated.

[0039] In the present invention, when the average diameter of the pores on the shell layer of the lithium adsorption material is tested by using a SEM electron microscope, 10 observation points are randomly selected for SEM testing, and the size of each observation area is not less than 500×500 μm, and the average value is calculated, and the long side diameter and short side diameter of all the pores in the observation area are statistically calculated, and the average pore diameter is the average value of the statistical long side diameter and short side diameter. The long side is the longest dimension of the pore, that is, the distance between the two points on the pore profile that are farthest apart; the short side is the length of the longest straight line between the intersection points that intersect the pore profile in the direction of the straight line perpendicular to the long side.

[0040] In the present invention, the average diameter of the pores in the shell of the lithium adsorption material measured by SEM electron microscopy is 0.01-2.5 μm, for example, 0.01 μm, 0.02 μm, 0.04 μm, 0.06 μm, 0.08 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.75 μm, 0.85 μm, 0.95 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm .6μm, 0.65μm, 0.7μm, 0.75μm, 0.8μm, 0.85μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, and ranges consisting of any two values.

[0041] In the present invention, the longest average length of the pores of the cross section of the lithium adsorption material measured by SEM electron microscopy is 1-7 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, and a range consisting of any two values; the shortest average length is 0.5-1.5 μm, for example, 0.05 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0. 35μm, 0.4μm, 0.45μm, 0.5μm, 0.55μm, 0.6μm, 0.65μm, 0.7μm, 0.75μm, 0.8μm, 0.85μm, 0.9μm, 0.95μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, and ranges consisting of any two values.

[0042] In the present invention, the thickness of the shell of the lithium adsorption material measured by SEM electron microscopy is 1-550 μm, for example, it can be 1 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, 300 μm, 310 μm, 320 μm, 330 μm, 340 μm, 350 μm, 360 μm, 370 μm, 380 μm, 390 μm, 400 μm, 410 μm, 420 μm, 430 μm, 440 μm, 450 μm, 460 μm, 470 μm, 480 μm, 490 μm, 500 μm, 510 μm, 520 μm, 530 μm, 540 μm, 550 μm, 560 μm, 570 μm, 580 μm, 590 μm, 600 μm, 610 μm, 620 μm, 630 μm, 640 μm, 650 μm, 660 μm, 670 μm 60μm, 270μm, 280μm, 290μm, 300μm, 310μm, 320μm, 330μm, 340μm, 350μm, 360μm, 370μm, 380μm, 390μm, 400μm, 410μm, 420μm, 430μm, 440μm, 450μm, 460μm, 470μm, 480μm, 490μm, 500μm, 510μm, 520μm, 530μm, 540μm, 550μm, and ranges consisting of any two values.

[0043] Furthermore, the average diameter of the pores in the shell of the lithium adsorption material measured by SEM electron microscopy is 0.1-0.5 μm;

[0044] The longest average length of the pores of the cross section of the lithium adsorption material measured by SEM electron microscopy is 2-5 μm; the shortest average length is 0.5-1.5 μm;

[0045] The thickness of the shell layer of the lithium adsorption material measured by SEM electron microscopy is 30-500 μm.

[0046] According to the present invention, the porosity of the lithium adsorption material is 60-80%.

[0047] In the present invention, when the porosity of the lithium adsorption material is controlled to meet the above range, the lithium adsorption material has a faster water mass transfer rate.

[0048] In the present invention, the porosity of the lithium adsorption material is 60-80%, for example, it can be 60%, 62%, 65%, 67%, 70%, 72%, 75%, 77%, 80%, and a range consisting of any two values.

[0049] Furthermore, the porosity of the lithium adsorption material is 65-75%.

[0050] According to the present invention, the lithium adsorption material is spherical and / or spherical-like.

[0051] In the present invention, the spherical or quasi-spherical shape means that the aspect ratio of the lithium adsorbent material particles is substantially in the range of 1-2. "Substantially" means that at least 90% of the lithium adsorbent material particles have an aspect ratio in the range of 1-2. The aspect ratio is the ratio of the longest dimension of the particle (the distance between the two points on the particle outline that are farthest apart, i.e., the longitudinal axis) to the length of the longest straight line between the intersection points where a plane perpendicular to the plane where the longitudinal axis is located intersects with the particle outline (the transverse axis). Preferably, at least 95% of the lithium adsorbent material has an aspect ratio of 1-2.

[0052] According to the present invention, the average particle size of the lithium adsorption material is 2-5 mm, for example, it can be 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, and a range consisting of any two values.

[0053] In the present invention, for spherical particles, the average particle size is the arithmetic average of the longitudinal axis and the transverse axis of the lithium adsorption material particles obtained by SEM electron microscope testing. Specifically, the average particle size of the lithium adsorption material = (longitudinal axis + transverse axis) / 2.

[0054] Furthermore, the average particle size of the lithium adsorption material is 3-4 mm.

[0055] According to the present invention, the specific surface area of ​​the lithium adsorption material is 10-100m 2 / g.

[0056] In the present invention, when the specific surface area of ​​the lithium adsorption material satisfies the above range, the lithium adsorption material can have a faster water mass transfer rate.

[0057] In the present invention, the specific surface area of ​​the lithium adsorption material is 10-100m 2 / g, for example, 10m 2 / g,15m 2 / g,20m 2 / g,25m 2 / g,30m 2 / g,35m 2 / g,40m 2 / g,45m 2 / g,50m 2 / g,55m 2 / g,60m 2 / g,65m 2 / g,70m 2 / g,75m 2 / g,80m 2 / g,85m 2 / g,90m 2 / g,95m 2 / g,100m2 / g, and any range of two values.

[0058] Furthermore, the specific surface area of ​​the lithium adsorption material is 35-65m 2 / g.

[0059] According to the present invention, the ratio of the sum of the surface areas S1 of the holes on the shell layer to the sum of the maximum cross-sectional areas S2 of the finger-shaped holes in the core body is 0.5-0.9:1.

[0060] In the present invention, in the lithium adsorption material, when the surface area S1 of the holes on the shell layer and the sum S2 of the maximum cross-sectional area of ​​the finger-shaped holes in the core body meet the above range, the lithium adsorption material has a faster water mass transfer rate inside the shell and the lithium ion sieve in the lithium adsorption material will not fall off under the pressure of the flushing water, ensuring that the lithium adsorption material maintains a high adsorption capacity while the lithium adsorption material is not damaged or broken.

[0061] In the present invention, the sum of the surface areas of the pores on the shell layer is tested on the lithium adsorption material using a SEM electron microscope, and 10 observation points are randomly selected for SEM testing, and the size of each observation area is not less than 500×500 μm, and the sum of the surface areas of the shell layer and the sum of the surface areas of all the pores on the shell layer within the observation range are calculated respectively. The histogram and magic wand tools in the Photoshop software can be selected to obtain the number of pixels representing the dark part of the membrane pores, and then the ratio thereof to the total number of pixels in the SEM image is calculated, which is the percentage of the sum of the surface areas S1 of the pores on the shell layer to the total surface area of ​​the shell layer.

[0062] The sum of the maximum cross-sectional areas of the finger-shaped pores in the core is analyzed by using Image J on the cross-sectional SEM image of the obtained lithium adsorption material, and the sum of the maximum cross-sectional areas of the finger-shaped pores S2 is measured and calculated.

[0063] In the present invention, the ratio of the sum of the surface areas S1 of the holes on the shell layer to the sum of the maximum cross-sectional areas S2 of the finger-like holes in the core body is 0.5-0.9:1, for example, it can be 0.5:1, 0.52:1, 0.54:1, 0.56:1, 0.58:1, 0.6:1, 0.62:1, 0.64:1, 0.66:1, 0.68:1, 0.7:1, 0.72:1, 0.74:1, 0.76:1, 0.78:1, 0.8:1, 0.82:1, 0.84:1, 0.86:1, 0.88:1, 0.9:1, and the range between any two values.

[0064] Furthermore, the ratio of the sum of the surface areas S1 of the holes on the shell layer to the sum of the maximum cross-sectional areas S2 of the finger-shaped holes in the core body is 0.6-0.8:1.

[0065] According to the present invention, the lithium adsorption material comprises a skeleton and a lithium ion sieve dispersed in the skeleton;

[0066] The skeleton includes polyvinyl chloride and polyacrylic acid.

[0067] Furthermore, the lithium ion sieve is a hydroxyl-modified lithium ion sieve, and the lithium ion sieve is connected to the framework via hydroxyl groups.

[0068] In the present invention, the lithium adsorption material includes a skeleton and a hydroxyl-modified lithium ion sieve dispersed in the skeleton, and the skeleton includes polyvinyl chloride (PVC) and polyacrylic acid, and the lithium ion sieve is connected to the skeleton through a hydroxyl group. Among them, the hydroxyl group in the lithium ion sieve has good compatibility with the polar group (-COOH) on the polyacrylic acid molecular chain and polyvinyl chloride, which can make the lithium ion sieve evenly dispersed in the skeleton containing polyvinyl chloride and polyacrylic acid, reducing the embedding phenomenon of the lithium ion sieve. At the same time, the carboxyl group (-COOH) on the polyacrylic acid molecular chain can promote lithium ion transfer, thereby significantly improving the adsorption and desorption rate of the lithium adsorption material.

[0069] In the present invention, the compound providing hydroxyl groups in the hydroxyl-modified lithium ion sieve forms a coating layer on the surface of the lithium ion sieve.

[0070] Furthermore, polyacrylic acid can inhibit the formation of salt crystals, especially the formation of salt crystals under high salt conditions, thereby reducing the phenomenon of pore blockage of the lithium adsorption material due to the formation of inorganic salt crystals in the internal pores of the lithium adsorption material during the cyclic adsorption and desorption process, and avoiding the phenomenon of polyvinyl chloride rupture caused by the exchange of water flow and salt during long-term use, thereby extending the cycle service life of the lithium adsorption material.

[0071] Furthermore, polyacrylic acid has excellent hydrophilicity and mechanical strength, and can significantly improve the mechanical properties of the skeleton containing polyacrylic acid and the swelling properties in a salt solution.

[0072] According to the present invention, based on the total weight of the lithium adsorption material, the content of the polyvinyl chloride is 16-67wt%; the content of the polyacrylic acid is 0.06-9wt%; and the content of the lithium ion sieve is 45-85wt%.

[0073] In the present invention, the total content of polyvinyl chloride, polyacrylic acid and lithium ion sieve in the lithium adsorption material is 100wt%.

[0074] In the present invention, based on the total weight of the lithium adsorption material, the content of the polyvinyl chloride is 16-67wt%, for example, it can be 16wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt%, 30wt%, 32wt%, 34wt%, 36wt%, 38wt%, 40wt%, 42wt%, 44wt%, 46wt%, 48wt%, 50wt%, 52wt%, 54wt%, 56wt%, 58wt%, 60wt%, 62wt%, 64wt%, 66wt%, 67wt%, and a range consisting of any two values; the content of the polyacrylic acid is 0.06-9wt%, for example, it can be 0 .06wt%, 0.08wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt%, 0.5wt%, 0.55wt%, 0.6wt%, 0.65wt%, 0.7wt%, 0.75wt%, 0.8wt%, 0.85wt%, 0.9wt%, and a range consisting of any two values; the content of the lithium ion sieve is 45-85wt%, for example, it can be 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, and a range consisting of any two values.

[0075] In the present invention, when the contents of polyvinyl chloride, polyacrylic acid and lithium ion sieve in the lithium adsorption material meet the above ranges, the lithium adsorption material can have high adsorption capacity, fast mass transfer rate, high mechanical properties, excellent anti-swelling properties, and can inhibit salt crystallization.

[0076] Furthermore, based on the total weight of the lithium adsorption material, the content of the polyvinyl chloride is 16-54wt%; the content of the polyacrylic acid is 0.9-9wt%; and the content of the lithium ion sieve is 45-80wt%.

[0077] According to the present invention, the thickness of the coating layer formed by the compound providing hydroxyl groups in the hydroxyl-modified lithium ion sieve is 1-5 nm.

[0078] In the present invention, when the thickness of the coating layer formed by the compound providing hydroxyl groups in the hydroxyl-modified lithium ion sieve is controlled to meet the above-mentioned range, it is possible to ensure excellent compatibility between the lithium ion sieve and the polymer, and the hydroxyl-modified lithium ion sieve thus obtained can be uniformly dispersed in the polymer skeleton, and the loading amount of the hydroxyl-modified lithium ion sieve in the polymer skeleton is increased, and the lithium ion sieve in the lithium adsorption material thus obtained has a high specific surface area, thereby improving the adsorption capacity of the lithium adsorption material.

[0079] In the present invention, the thickness of the coating layer formed by the compound providing hydroxyl groups in the hydroxyl-modified lithium ion sieve is 1-5 nm, for example, it can be 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, and a range consisting of any two values.

[0080] Furthermore, the thickness of the coating layer formed by the compound providing hydroxyl groups in the hydroxyl-modified lithium ion sieve is 3-5 nm.

[0081] In the present invention, the thickness of the coating layer formed by the compound providing hydroxyl groups in the hydroxyl-modified lithium ion sieve is measured by SEM electron microscope observation.

[0082] According to the present invention, the hydroxyl-modified lithium ion sieve is a polyphenol-modified lithium ion sieve.

[0083] In the present invention, when the hydroxyl-modified lithium ion sieve is a polyphenol-modified lithium ion sieve, the compatibility between the lithium ion sieve and the polymer is improved, so that the lithium ion sieve has better dispersibility in the polymer skeleton, and the modification conditions are milder, which can make the lithium adsorption material have a high adsorption capacity.

[0084] According to the present invention, the polyphenols are selected from at least one of tannic acid, tea polyphenols, apple polyphenols, grape polyphenols, eriodictyol, naringenin, epicatechin, luteolin, naringenin, kaempferol, myricetin and genistein, preferably at least one of tannic acid, tea polyphenols and apple polyphenols.

[0085] According to the present invention, the lithium ion sieve is selected from titanium-based lithium ion sieves and / or manganese-based ion sieves.

[0086] According to the present invention, the lithium ion is selected from LiMn 2 O 4 , Li 1.6 Mn 1.6 O 4 , Li 1.33 Mn 1.67 O 4 , Li 4 Mn 5 O 12 、LiMnO 2 , Li 2 TiO 3 , Li 1.33 Ti 1.66 O 4 and Li 4 Ti 5 O 12 At least one of .

[0087] According to the present invention, the water content of the hydroxyl-modified lithium ion sieve is less than or equal to 0.5 wt %.

[0088] In the present invention, when the moisture content of the hydroxyl-modified lithium ion sieve is controlled to meet the above range, it is possible to avoid phase separation between the polymer and the hydroxyl-modified lithium ion sieve due to the presence of water, thereby causing the dispersibility of the hydroxyl-modified lithium ion sieve in the skeleton to deteriorate.

[0089] In the present invention, the water content of the hydroxyl-modified lithium ion sieve refers to the free water content in the hydroxyl-modified lithium ion sieve.

[0090] In the present invention, the moisture content of the hydroxyl-modified lithium ion sieve is less than or equal to 0.5wt%, for example, it can be 0.5wt%, 0.45wt%, 0.4wt%, 0.35wt%, 0.3wt%, 0.25wt%, 0.2wt%, 0.15wt%, 0.1wt%, and a range consisting of any two values.

[0091] Furthermore, the water content of the hydroxyl-modified lithium ion sieve is 0.1-0.3 wt %.

[0092] According to the present invention, the average particle diameter of the lithium ion sieve in the cross section of the lithium adsorption material measured by SEM electron microscope is less than or equal to 2.5 μm.

[0093] In the present invention, when the average particle diameter of the lithium ion sieve in the cross section of the lithium adsorption material satisfies the above range, the effective adsorption performance of the lithium ion sieve is maximized, so that the lithium adsorption material has a large adsorption capacity and a high desorption efficiency of lithium ions.

[0094] In the present invention, the average particle diameter of the lithium ion sieve in the lithium adsorption material refers to the average diameter of a single lithium ion sieve or the average diameter of an aggregate formed by multiple lithium ion sieve particles. However, as long as the average particle diameter of a single lithium ion sieve particle and an aggregate formed by multiple lithium ion sieve particles in the cross section of the lithium adsorption material meets the above range, it indicates that the lithium ion sieve is uniformly distributed in the lithium adsorption material.

[0095] In the present invention, the average particle diameter of the lithium ion sieve in the lithium adsorption material is measured by a SEM electron microscope, and 10 observation points are randomly selected for scanning electron microscope testing, and the size of each observation area is not less than 500×500 μm. When the lithium ion sieve is completely not agglomerated, the average particle diameter is the average particle diameter of a single lithium ion sieve, and when the lithium ion sieve is partially agglomerated, the average particle diameter is the maximum particle diameter of the aggregate.

[0096] In the present invention, the average particle diameter of the lithium ion sieve in the cross section of the lithium adsorption material measured by SEM electron microscopy is less than or equal to 2.5 μm, for example, it can be 2.5 μm, 2 μm, 1.5 μm, 1 μm, 0.5 μm, 0.4 μm, 0.3 μm, 0.2 μm, 0.1 μm, and a range consisting of any two values.

[0097] Furthermore, the average particle diameter of the lithium ion sieve in the cross section of the lithium adsorption material measured by SEM electron microscope is less than or equal to 1.5 μm, preferably 0.1-1.5 μm.

[0098] According to the present invention, based on the total surface area of ​​the shell layer of the lithium adsorption material, the sum S1 of the surfaces of the pores present in the shell layer is 30-90%.

[0099] In the present invention, when the sum S1 of the surfaces of the pores existing on the shell layer covering the surface of the core in the lithium adsorption material satisfies the above range, the lithium adsorption material has a fast water adsorption mass transfer rate, a fast adsorption rate, a high desorption efficiency, and a small decrease in cyclic performance.

[0100] In the present invention, the total area of ​​the pores present in the shell layer refers to the sum of the surface areas of all the pores present in the shell layer.

[0101] In the present invention, the total surface area of ​​the shell layer of the lithium adsorption material and the sum of the surface areas of the holes on the shell layer S1 are measured by SEM electron microscope. Specifically, the lithium adsorption material is tested by SEM electron microscope, and 10 observation points are randomly selected for SEM test. The size of each observation area is not less than 500×500 μm, and the sum of the surface areas of the shell layer and the sum of the areas of all holes on the shell layer within the observation range are calculated respectively. The histogram and magic wand tools in Photoshop software can be selected to obtain the number of pixels representing the dark part of the membrane pores, and then the ratio thereof to the total number of pixels in the SEM image is calculated, which is the percentage of the sum of the surface areas S1 of the holes on the shell layer to the total surface area of ​​the shell layer.

[0102] In the present invention, based on the total surface area of ​​the shell layer of the lithium adsorption material, the sum S1 of the surfaces of the pores present in the shell layer is 30-90%, for example, it can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, and a range consisting of any two values.

[0103] Furthermore, based on the total surface area of ​​the shell layer of the lithium adsorption material, the sum S1 of the surfaces of the pores existing in the shell layer is 50-90%.

[0104] A second aspect of the present invention provides a method for preparing a lithium adsorption material, characterized in that the method comprises the following steps:

[0105] (1) mixing polyvinyl chloride, polyacrylic acid, lithium ion sieve and oil phase solvent to obtain a mixed solution;

[0106] (2) Under the conditions of temperature of 20-60° C. and humidity of 40-80%, the mixed solution is added dropwise to an aqueous solvent to obtain a lithium adsorption material.

[0107] In the present invention, the above method is used to prepare the lithium adsorption material. Specifically, under specific temperature and humidity conditions, a mixed solution containing polyvinyl chloride, polyacrylic acid and lithium ion sieve is added dropwise to an aqueous solvent to obtain the lithium adsorption material described in the first aspect of the present invention. Specifically, under specific temperature and humidity conditions, the rates of internal and surface phase transformations are different, and a structure with small pores on the surface and large pores on the inside is prepared, so that the lithium adsorption material has a faster water mass transfer rate inside the shell and will not leak the internal lithium ion sieve powder under the pressure of the flushing water. The lithium adsorption material thus prepared has a high adsorption capacity and a long service life.

[0108] According to the present invention, the lithium ion sieve is selected from titanium-based lithium ion sieves and / or manganese-based ion sieves.

[0109] According to the present invention, the lithium ion is selected from LiMn 2 O 4 , Li 1.6 Mn 1.6 O 4 , Li 1.33 Mn 1.67 O 4 , Li 4 Mn 5 O 12 、LiMnO 2 , Li 2 TiO 3 , Li 1.33 Ti 1.66 O 4 and Li 4 Ti 5 O 12 At least one of .

[0110] In the present invention, the average particle size of the lithium ion sieve is 0.1-1 μm, for example, it can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, and a range consisting of any two values.

[0111] According to the present invention, in step (1), the weight average molecular weight of the polyvinyl chloride is 50,000-110,000 g / mol, for example, it can be 50,000 g / mol, 55,000 g / mol, 60,000 g / mol, 65,000 g / mol, 70,000 g / mol, 75,000 g / mol, 80,000 g / mol, 85,000 g / mol, 90,000 g / mol, 95,000 g / mol, 100,000 g / mol, 105,000 g / mol, 110,000 g / mol, and a range consisting of any two values.

[0112] Furthermore, the weight average molecular weight of the polyvinyl chloride is 70,000-90,000 g / mol.

[0113] In the present invention, there is no particular limitation on the type of the oil phase solvent, and conventional oil phase solvents in the art may be used, such as at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.

[0114] According to the present invention, the weight average molecular weight of the polyacrylic acid is 100,000-1.3 million g / mol.

[0115] In the present invention, the polyacrylic acid having a specific weight average molecular weight is selected, so that the interpenetrating network structure formed between the polyacrylic acid and the polyvinyl chloride molecular chains has improved mechanical strength, and has the effects of inhibiting salt crystallization, promoting lithium ion transfer and resisting swelling, and finally the mechanical properties, adsorption capacity for lithium and anti-swelling properties of the prepared lithium adsorption material are significantly improved.

[0116] In the present invention, the weight average molecular weight of the polyacrylic acid is 100,000-1.3 million g / mol, for example, 100,000 g / mol, 150,000 g / mol, 200,000 g / mol, 250,000 g / mol, 300,000 g / mol, 350,000 g / mol, 400,000 g / mol, 450,000 g / mol, 500,000 g / mol, 550,000 g / mol, 600,000 g / mol, 650,000 g / mol, 700,000 g / mol, 750,000 g / mol, 800,000 g / mol, 850,000 g / mol, 900,000 g / mol, 950,000 g / mol, 1,000,000 g / mol, 1,100,000 g / mol, 1,200,000 g / mol, 1,300,000 g / mol, and a range consisting of any two values.

[0117] Furthermore, the weight average molecular weight of the polyacrylic acid is 1-1.3 million g / mol.

[0118] According to the present invention, in step (1), the amounts of the polyvinyl chloride, the polyacrylic acid and the lithium ion sieve are such that, based on the total weight of the lithium adsorption material, the content of the polyvinyl chloride is 16-67wt%; the content of the polyacrylic acid is 0.06-9wt%; and the content of the lithium ion sieve is 45-85wt%.

[0119] In the present invention, when the amounts of polyvinyl chloride, polyacrylic acid and lithium ion sieve are controlled to meet the above range, the interpenetrating network structure formed between the polyacrylic acid and polyvinyl chloride molecular chains can have improved mechanical strength, and at the same time has the effects of inhibiting salt crystallization, promoting lithium ion transfer and resisting swelling, and ultimately the mechanical properties, adsorption capacity for lithium and anti-swelling properties of the prepared lithium adsorption material are significantly improved.

[0120] Furthermore, in step (1), the amounts of the polyvinyl chloride, the polyacrylic acid and the lithium ion sieve are such that, based on the total weight of the lithium adsorption material, the content of the polyvinyl chloride is 16-54wt%; the content of the polyacrylic acid is 0.9-9wt%; and the content of the lithium ion sieve is 45-80wt%.

[0121] In the present invention, there is no particular limitation on the mixing conditions of step (1), as long as the polyvinyl chloride, polyacrylic acid, lithium ion sieve and oil phase solvent can be fully mixed to obtain a mixed solution, for example, the mixing is carried out at 20-70° C. under stirring conditions.

[0122] In a specific embodiment of the present invention, in step (1), in order to make the materials in the mixed liquid fully mixed and uniform, preferably, during the mixing process, a step-by-step feeding method is adopted. Specifically, after the polyvinyl chloride, polyacrylic acid and the oil phase solvent are mixed, the lithium ion sieve is added to the above mixed product to obtain the mixed liquid.

[0123] In the present invention, in step (2), the temperature is 20-60°C, for example, it can be 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, and a range consisting of any two values; the humidity is 40-80%, for example, it can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, and a range consisting of any two values.

[0124] Furthermore, in step (2), the mixed solution is added dropwise into the aqueous phase solvent at a temperature of 35-60° C. and a humidity of 60-80%.

[0125] According to the present invention, the aqueous phase solvent is selected from at least one of water, ethanol and acetic acid, preferably water.

[0126] According to the present invention, in order to further improve the dispersibility of the lithium ion sieve in the polymer network structure formed by polyvinyl chloride and polyacrylic acid, preferably, the lithium ions are hydroxyl-modified lithium ion sieve.

[0127] According to the present invention, the lithium ion sieve is modified by using an aqueous solution containing a hydroxyl compound, and the hydroxyl-modified lithium ion sieve is obtained after solid-liquid separation and drying.

[0128] According to the present invention, the hydroxyl-containing compound is a polyphenol; preferably selected from at least one of tannic acid, tea polyphenols, apple polyphenols, grape polyphenols, eriodictyol, naringenin, epicatechin, luteolin, naringenin, kaempferol, myricetin and genistein, preferably at least one of tannic acid, tea polyphenols and apple polyphenols.

[0129] According to the present invention, the concentration of the aqueous solution containing hydroxyl compounds is 0.05 mg / L-1 mg / L, for example, it can be 0.05 mg / L, 0.15 mg / L, 0.2 mg / L, 0.25 mg / L, 0.3 mg / L, 0.35 mg / L, 0.4 mg / L, 0.45 mg / L, 0.5 mg / L, 0.55 mg / L, 0.6 mg / L, 0.65 mg / L, 0.7 mg / L, 0.75 mg / L, 0.8 mg / L, 0.85 mg / L, 0.9 mg / L, 0.95 mg / L, 1 mg / L, and a range consisting of any two values.

[0130] In the present invention, when the concentration of the aqueous solution containing hydroxyl compounds is controlled to meet the above range, it can ensure that the hydroxyl groups form a coating layer with a suitable thickness on the surface of the lithium ion sieve, ensuring that the hydroxyl-modified lithium ion sieve can have good dispersibility in the polymer skeleton.

[0131] According to the present invention, the mass ratio of the lithium ion sieve to the hydroxyl-containing compound is 1:0.01-0.3.

[0132] In the present invention, when the mass ratio of the lithium ion sieve to the hydroxyl-containing compound is controlled to meet the above range, it can ensure that the lithium ion sieve and the hydroxyl-containing compound fully react, and the hydroxyl-containing compound can form a uniform coating layer on the surface of the lithium ion sieve, thereby significantly improving the dispersibility of the prepared hydroxyl-modified lithium ion sieve.

[0133] In the present invention, the mass ratio of the lithium ion sieve to the hydroxyl-containing compound is 1:0.01-0.3, for example, it can be 1:0.01, 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, and a range consisting of any two values.

[0134] Furthermore, the mass ratio of the lithium ion sieve to the hydroxyl-containing compound is 1:0.05-0.08.

[0135] According to the present invention, the modification conditions include: reaction time of 30min-4h, for example, 30min, 40min, 50min, 60min, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h, 2.5h, 3h, 3.5h, 4h, and ranges consisting of any two values; reaction temperature of 25-40°C, for example, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, and ranges consisting of any two values.

[0136] In the present invention, the modification reaction is carried out under the above conditions to ensure sufficient reaction between the lithium ion sieve and the hydroxyl-containing compound, and the hydroxyl-containing compound can form a uniform coating layer on the surface of the lithium ion sieve, thereby significantly improving the dispersibility of the prepared hydroxyl-modified lithium ion sieve.

[0137] In the present invention, there is no particular limitation on the solid-liquid separation and drying methods and conditions. Conventional solid-liquid separation in the art, such as centrifugal separation, and conventional drying methods and conditions can be used, as long as the moisture content of the hydroxy-modified lithium ion sieve after drying meets the requirements of the present invention.

[0138] According to the present invention, the method further comprises: a step of washing the lithium adsorption material with an acidic solution.

[0139] In the present invention, the lithium adsorption material is a lithium adsorption material precursor, and the lithium adsorption material is washed with an acidic solution to make the Li + and H + Exchange to activate the precursor and obtain H-type lithium ion sieve, such as Li 1.33 Mn 1.67 O 4 Convert to H 1.33 Mn 1.67 O 4 The obtained H-type lithium ion sieve has a specific adsorption effect on lithium ions.

[0140] Furthermore, under the action of a peristaltic pump, an acidic solution is used to circulate and wash the lithium adsorption material.

[0141] Furthermore, the acidic solution is selected from at least one of hydrochloric acid, phosphoric acid and sulfuric acid.

[0142] Furthermore, H +Ion meter, the concentration of the acidic solution is 0.1-1 mol / L, for example, it can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, and a range consisting of any two values.

[0143] Further, the flow rate of the peristaltic pump is 1-25BV / h, for example, it can be 1BV / h, 5BV / h, 10BV / h, 15BV / h, 20BV / h, 25BV / h, and a range consisting of any two values, and the cycle time is 1-48h, for example, it can be 1h, 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h, 36h, 38h, 40h, 42h, 44h, 46h, 48h, and a range consisting of any two values.

[0144] In the present invention, when the conditions of the circulating washing or the concentration of the acidic solution are controlled to meet the above range, it is possible to ensure ion exchange without destroying the structure of the lithium ion sieve, thereby ensuring that the washed lithium adsorption material has high mechanical strength, high adsorption capacity for lithium and excellent anti-swelling performance.

[0145] In a specific embodiment of the present invention, the concentration of the acidic solution is 0.1-0.5 mol / L; the flow rate of the peristaltic pump is 2-10 BV / h, and the circulation time is 4-24 h.

[0146] The third aspect of the present invention provides a lithium adsorption material prepared by the above method.

[0147] A fourth aspect of the present invention provides an application of the lithium adsorption material in lithium extraction, preferably in a liquid environment.

[0148] In the present invention, unless otherwise specified, the average diameter, average particle size, etc. refer to the volume average diameter and volume average particle size of particles.

[0149] The present invention will be described in detail below by way of examples. In the following examples,

[0150] The morphology of the granulated products was characterized by scanning electron microscopy (SEM, S-4800, Japan).

[0151] The thickness of the shell and the average diameter of the pores in the shell were measured by scanning electron microscopy.

[0152] The sum of the surface areas of the holes on the shell layer S1 and the sum of the maximum cross-sectional areas of the finger-shaped holes in the core S2 were analyzed by ImageJ to measure the sum of the surface areas of the holes and the sum of the maximum cross-sectional areas of the finger-shaped holes in the core.

[0153] The longest average length and the shortest average length of the finger-like pores contained in the core of the lithium adsorption material are measured by scanning electron microscopy and calculated.

[0154] In the present invention, the average particle diameter of the lithium ion sieve in the lithium adsorption material is measured by SEM electron microscope. When the lithium ion sieve is not agglomerated at all, the average particle diameter is the average particle diameter of a single lithium ion sieve. When the lithium ion sieve is partially agglomerated, the average particle diameter is the average particle diameter of the largest aggregate.

[0155] The sum of the surface areas of the shell layer of the lithium adsorption material and the sum of the surface areas of the pores on the shell layer are measured using a SEM electron microscope. Specifically, when the density of the pores on the shell layer of the lithium adsorption material is tested using a SEM electron microscope, 10 observation points are randomly selected for SEM testing, and the size of each observation area is not less than 500×500 μm. The sum of the surface areas of the shell layer and the sum of the surface areas of all the pores on the shell layer within the observation range are calculated respectively. The histogram and magic wand tools in the Photoshop software can be selected to obtain the number of pixels representing the dark part of the membrane pores, and then the ratio thereof to the total number of pixels in the SEM image is calculated, which is the percentage of the sum of the surface areas S1 of the pores on the shell layer to the total surface area of ​​the shell layer.

[0156] The average particle size of the lithium adsorbent material and the hydroxyl-modified ion sieve was measured by scanning electron microscopy.

[0157] The porosity is measured by a mercury intrusion instrument AutoPore IV 9500 (Micromeritics Instruments, USA). The specific test method is to press mercury into the pores of the lithium adsorption material at a pressure of 0.1 to 60 kPa, and obtain the porosity through the mercury change curve data.

[0158] The specific surface area is determined by the BET method, which is to measure the surface area of ​​lithium adsorbent material to N at 77K. 2 The adsorption-desorption isotherms were fitted to obtain the BET specific surface area.

[0159] The contents of polyvinyl chloride, polyacrylic acid and hydroxyl-modified lithium ion sieve in the lithium adsorption material are obtained by measuring the content of elements using X-ray photoelectron spectroscopy (XPS), wherein the content of PVC in the lithium adsorption material is calculated from the content of Cl element, the content of hydroxyl-modified lithium ion sieve is calculated from the content of metal Mn or Ti, and the content of polyacrylic acid = the weight of lithium adsorption material particles - the content of polyvinyl chloride - the content of hydroxyl-modified lithium ion sieve.

[0160] The thickness of the coating layer formed by polyphenol in the polyphenol-modified lithium ion sieve is measured by transmission electron microscopy.

[0161] The moisture content of the hydroxyl-modified lithium ion sieve was measured using a moisture meter.

[0162] Adsorption-desorption cycle: The obtained lithium adsorption material particles (4 g) were loaded into a glass column and acid-washed (using H + 0.5mol / L hydrochloric acid was washed at a rate of 2BV / h for 24h), and a mixed solution of lithium chloride and magnesium chloride (lithium ion content 100mg / L, magnesium ion concentration 20000mg / L, ammonia water was used to adjust the pH of the mixed solution to 9.5, V=400mL) was pumped in at a flow rate of 2BV / h by a peristaltic pump for dynamic adsorption-desorption cycle adsorption for 24h. Then a peristaltic pump was used to pump 0.5M hydrochloric acid (200mL) at a flow rate of 2BV / h for 24h to desorb lithium ions from the particles. Then washing with deionized water until neutral is one cycle. During one adsorption process, the change of adsorption capacity over time was monitored and the saturated adsorption capacity Q was calculated. The calculation formula is as follows:

[0163]

[0164] Where Q is the saturated adsorption capacity, in mg / g, which reflects the adsorption amount when the adsorption reaches equilibrium; C 0 and C are the initial and saturated lithium ion concentrations in the solution, respectively, in mg / L, V is the volume of the adsorption solution, in L; m is the mass of the granular adsorbent, in g. Ion concentrations were determined using ion chromatography (ICS-1100, DIONEX, America).

[0165] Lithium ion desorption efficiency D Li+ :D Li+ (%)=(c 1 *V 2 ) / m*100%, where c 1 is the concentration of lithium in the desorption solution, mg / L; V 2 is the volume of the desorption solution, L; m is the mass of the adsorbed lithium ions, g.

[0166] The adsorption capacity decrease rate after 30 cycles of operation is calculated according to the following formula:

[0167] The adsorption capacity decrease rate after 30 cycles of operation, % = (Q1-Q30) / Q1*100%, Q1 is the first adsorption capacity, Q30 is the 30th adsorption capacity.

[0168] Water mass transfer rate: the time it takes for a unit mass of dry lithium adsorbent material (mass m0) to reach a completely water-absorbed state (m, mass no longer increases) when it is immersed in water, in units of min / g.

[0169] Mechanical properties: After 30 cycles of adsorption and desorption (adsorption under the condition of adjusting the pH of the mixed solution to 9.5 with ammonia water, and desorption with 0.5M hydrochloric acid), SEM observation showed that there were no cracks on the surface of the lithium adsorption material.

[0170] Anti-swelling performance: A unit mass of lithium adsorption material was immersed in a high salt solution (lithium ion content 100 mg / L, magnesium ion concentration 20000 mg / L) for 48 hours, and the volume change rate was used to characterize the anti-swelling performance of the lithium adsorption material, where volume change rate (%) = (volume after swelling - volume before swelling) / volume before swelling × 100%.

[0171] In the following examples and comparative examples, all reagents were purchased from Bailingwei Technology Co., Ltd.

[0172] Example 1

[0173] (1) Take powder Li 1.33 Mn 1.67 O 4 The obtained solid phase material was dried, ground and sieved to obtain a hydroxyl-modified (polyphenol-modified) lithium ion sieve having a water content of 0.3 wt % and a coating layer formed by hydroxyl groups on the surface of the lithium ion sieve having a thickness of 5 nm.

[0174] (2) Weigh 10 g of polyvinyl chloride (weight average molecular weight 62,000 g / mol) powder, 2 g of polyacrylic acid (weight average molecular weight 350,000 g / mol) and 88 g of DMF, place them in a beaker and stir, heat to 60°C, cool to 30°C after dissolving, add 40 g of hydroxyl-modified (polyphenol-modified) lithium ion sieve, stir and mix at 30°C to obtain a mixed solution.

[0175] (3) The mixed solution was added dropwise to water at a temperature of 30°C and a humidity of 56% to obtain lithium adsorption material particles A1. The moisture content of the hydroxyl-modified lithium ion sieve and the thickness of the coating layer formed by the hydroxyl group on the surface of the lithium ion sieve are shown in Table 1.

[0176] The microscopic morphology parameters of the lithium adsorption material particles are shown in Table 2, and the contents of polyvinyl chloride, polyacrylic acid and hydroxyl-modified lithium ion sieve in the lithium adsorption material particles are shown in Table 2.

[0177] Example 2

[0178] (1) Take powder Li 1.33 Mn 1.67 O 4 The obtained solid phase material was dried, ground and sieved to obtain a hydroxyl-modified (polyphenol-modified) lithium ion sieve having a water content of 0.3 wt % and a coating layer formed by hydroxyl groups on the surface of the lithium ion sieve having a thickness of 3 nm.

[0179] (2) Weigh 8 g of polyvinyl chloride (weight average molecular weight 62,000 g / mol) powder, 0.2 g of polyacrylic acid (weight average molecular weight 350,000 g / mol) and 91.8 g of DMF into a beaker and stir, heat to 60°C, cool to 30°C after dissolving, add 10 g of hydroxyl-modified (polyphenol-modified) lithium ion sieve, stir and mix at 30°C to obtain a mixed solution.

[0180] (3) Under the conditions of temperature of 55°C and humidity of 75%, the second mixed solution was added dropwise to water to obtain lithium adsorption material particles A2. The moisture content of the hydroxyl-modified lithium ion sieve and the thickness of the coating layer formed by the hydroxyl group on the surface of the lithium ion sieve are shown in Table 1.

[0181] The microscopic morphology parameters of the lithium adsorption material particles are shown in Table 2, and the contents of polyvinyl chloride, polyacrylic acid and hydroxyl-modified lithium ion sieve in the lithium adsorption material particles are shown in Table 2.

[0182] Example 3

[0183] (1) Take powder Li 1.33 Mn 1.67 O 4 The obtained mixture was stirred at 30°C for 1 hour and then centrifuged. The solid phase material was dried, ground and sieved to obtain a hydroxyl-modified (polyphenol-modified) lithium ion sieve with a water content of 0.3wt% and a coating layer formed by hydroxyl groups on the surface of the lithium ion sieve with a thickness of 3.2nm.

[0184] (2) Weigh 12 g of polyvinyl chloride (weight average molecular weight 62,000 g / mol) powder, 3 g of polyacrylic acid (weight average molecular weight 350,000 g / mol) and 85 g of DMF, place them in a beaker and stir, heat to 60°C, cool to 30°C after dissolving, add 20 g of hydroxyl-modified (polyphenol-modified) lithium ion sieve, stir and mix at 30°C to obtain a mixed solution.

[0185] (3) Under the conditions of temperature of 40°C and humidity of 42%, the mixed solution was added dropwise to water to obtain lithium adsorption material particles A3. The moisture content of the hydroxyl-modified lithium ion sieve and the thickness of the coating layer formed by the hydroxyl group on the surface of the lithium ion sieve are shown in Table 1.

[0186] The microscopic morphology parameters of the lithium adsorption material particles are shown in Table 2, and the contents of polyvinyl chloride, polyacrylic acid and hydroxyl-modified lithium ion sieve in the lithium adsorption material particles are shown in Table 2.

[0187] Example 4

[0188] (1) Take powder Li 1.33 Mn 1.67 O 4 The obtained mixture was stirred at 30°C for 1 hour and then centrifuged. The solid phase material was dried, ground and sieved to obtain a hydroxyl-modified (polyphenol-modified) lithium ion sieve with a water content of 0.3wt% and a coating layer of 2nm formed by hydroxyl groups on the surface of the lithium ion sieve.

[0189] (2) Weigh 6 g of polyvinyl chloride (weight average molecular weight 62,000 g / mol) powder, 0.1 g of polyacrylic acid (weight average molecular weight 350,000 g / mol) and 93.9 g of DMF, place in a beaker and stir, heat to 60°C, cool to 30°C after dissolution, add 5 g of hydroxyl-modified (polyphenol-modified) lithium ion sieve, stir and mix at 30°C to obtain a mixed solution.

[0190] (4) The mixed solution was added dropwise to water at a temperature of 30°C and a humidity of 52% to obtain lithium adsorption material particles A4. The moisture content of the hydroxyl-modified lithium ion sieve and the thickness of the coating layer formed by the hydroxyl group on the surface of the lithium ion sieve are shown in Table 1.

[0191] The microscopic morphology parameters of the lithium adsorption material particles are shown in Table 2, and the contents of polyvinyl chloride, polyacrylic acid and hydroxyl-modified lithium ion sieve in the lithium adsorption material particles are shown in Table 2.

[0192] Example 5

[0193] (1) Same as Example 1.

[0194] (2) Weigh 10 g of polyvinyl chloride (weight average molecular weight 62,000 g / mol) powder, 0.1 g of polyacrylic acid (weight average molecular weight 350,000 g / mol) and 93.9 g of DMF, place them in a beaker and stir, heat to 60°C, cool to 30°C after dissolving, add 5 g of hydroxyl-modified (polyphenol-modified) lithium ion sieve, stir and mix at 30°C to obtain a mixed solution.

[0195] (3) The lithium adsorption material particles A5 were obtained in the same manner as in Example 1. The moisture content of the hydroxyl-modified lithium ion sieve and the thickness of the coating layer formed by the hydroxyl groups on the surface of the lithium ion sieve are shown in Table 1.

[0196] The microscopic morphology parameters of the lithium adsorption material particles are shown in Table 2, and the contents of polyvinyl chloride, polyacrylic acid and hydroxyl-modified lithium ion sieve in the lithium adsorption material particles are shown in Table 2.

[0197] Example 6

[0198] (1) Take powder Li 1.33 Mn 1.67 O 4 The obtained solid phase material was dried, ground and sieved to obtain a hydroxyl-modified (polyphenol-modified) lithium ion sieve having a water content of 0.3 wt % and a coating layer formed by hydroxyl groups on the surface of the lithium ion sieve having a thickness of 2 nm.

[0199] (2) Weigh 10 g of polyvinyl chloride (weight average molecular weight 62,000 g / mol) powder, 0.1 g of polyacrylic acid (weight average molecular weight 350,000 g / mol) and 93.9 g of DMF, place them in a beaker and stir, heat to 60°C, cool to 30°C after dissolving, add 50 g of hydroxyl-modified (polyphenol-modified) lithium ion sieve, stir and mix at 30°C to obtain a mixed solution.

[0200] (3) Under the conditions of temperature of 30°C and humidity of 56%, the mixed solution was added dropwise to water to obtain lithium adsorption material particles A6. The moisture content of the hydroxyl-modified lithium ion sieve and the thickness of the coating layer formed by the hydroxyl group on the surface of the lithium ion sieve are shown in Table 1.

[0201] The microscopic morphology parameters of the lithium adsorption material particles are shown in Table 2, and the contents of polyvinyl chloride, polyacrylic acid and hydroxyl-modified lithium ion sieve in the lithium adsorption material particles are shown in Table 2.

[0202] Example 7

[0203] Same as Example 1, in step (1), tannic acid is replaced with polyethylene glycol (molecular weight 1000 g / mol), to obtain a hydroxyl-modified (alcohol hydroxyl-modified) lithium ion sieve, the water content is 0.3wt%, and the thickness of the coating layer formed by the hydroxyl group on the surface of the lithium ion sieve is 3nm. The lithium adsorption material A7 is obtained. Among them, the water content of the hydroxyl-modified lithium ion sieve and the thickness of the coating layer formed by the hydroxyl group on the surface of the lithium ion sieve are shown in Table 1.

[0204] The microscopic morphology parameters of the lithium adsorption material particles are shown in Table 2, and the contents of polyvinyl chloride, polyacrylic acid and hydroxyl-modified lithium ion sieve in the lithium adsorption material particles are shown in Table 2.

[0205] Example 8

[0206] The same as Example 1, wherein the weight average molecular weight of polyvinyl chloride is 78,000 g / mol, and the weight average molecular weight of polyacrylic acid is 1.3 million g / mol, to obtain lithium adsorption material A8. The moisture content of the hydroxyl-modified lithium ion sieve is shown in Table 1 as the thickness of the coating layer formed by the hydroxyl group on the surface of the lithium ion sieve.

[0207] The microscopic morphology parameters of the lithium adsorption material particles are shown in Table 2, and the contents of polyvinyl chloride, polyacrylic acid and hydroxyl-modified lithium ion sieve in the lithium adsorption material particles are shown in Table 2.

[0208] Example 9

[0209] The same as Example 1, without the modification in step (1), the lithium ion sieve was directly used to prepare the lithium adsorption material A9. The water content of the lithium ion sieve is shown in Table 1.

[0210] The microscopic morphology parameters of the lithium adsorption material particles are shown in Table 2, and the contents of polyvinyl chloride, polyacrylic acid and hydroxyl-modified lithium ion sieve in the lithium adsorption material particles are shown in Table 2.

[0211] Example 10

[0212] Same as Example 1, in step (1), tannic acid is replaced with tea polyphenols. A hydroxyl-modified (phenolic hydroxyl-modified) lithium ion sieve is obtained, the moisture content is 0.3wt%, and the thickness of the coating layer formed by the hydroxyl group on the surface of the lithium ion sieve is 3nm. The lithium adsorption material A10 is obtained. Among them, the moisture content of the hydroxyl-modified lithium ion sieve and the thickness of the coating layer formed by the hydroxyl group on the surface of the lithium ion sieve are shown in Table 1.

[0213] The microscopic morphology parameters of the lithium adsorption material particles are shown in Table 2, and the contents of polyvinyl chloride, polyacrylic acid and hydroxyl-modified lithium ion sieve in the lithium adsorption material particles are shown in Table 2.

[0214] Embodiment 11

[0215] Same as in Example 1, in step (1), the lithium ion sieve is replaced by Li 2 TiO 3 (average particle size is 1 μm), a hydroxyl-modified lithium ion sieve is obtained, the water content is 0.3wt%, and the thickness of the coating layer formed by the hydroxyl group on the lithium ion sieve is 4.9nm. The lithium adsorption material A11 is obtained. Among them, the water content of the hydroxyl-modified lithium ion sieve and the thickness of the coating layer formed by the hydroxyl group on the surface of the lithium ion sieve are shown in Table 1.

[0216] The microscopic morphology parameters of the lithium adsorption material particles are shown in Table 2, and the contents of polyvinyl chloride, polyacrylic acid and hydroxyl-modified lithium ion sieve in the lithium adsorption material particles are shown in Table 2.

[0217] Comparative Example 1

[0218] The same as Example 1, without adding polyacrylic acid, to obtain lithium adsorption material D1.

[0219] Comparative Example 2

[0220] Same as in Example 1, in step (4), the temperature is 20° C. and the humidity is 10%. Thus, lithium adsorption material D2 is obtained.

[0221] Comparative Example 3

[0222] The same as in Example 1, except that the modification operation in step (1) was not performed, and in step (4), the temperature was 20° C. and the humidity was 10%, thereby obtaining a lithium adsorption material D3.

[0223] Comparative Example 4

[0224] The same as Example 1, without the modification operation of step (1), the polyacrylic acid was replaced with polyacrylonitrile (weight average molecular weight of 80,000 g / mol), to obtain lithium adsorption material D4.

[0225] Comparative Example 5

[0226] Granulation was performed by extrusion. 525 g PVC (weight average molecular weight 62,000 g / mol) and 175 g thermoplastic acrylic resin (weight average molecular weight 120,000 g / mol) were melted at 170°C. Then 250 g Li 1.33 Mn 1.67 O 4 The powder (average particle size 0.5 μm) was stirred evenly and then extruded and cooled to form a lithium adsorption material D5.

[0227] Table 1

[0228]

[0229]

[0230] Table 2

[0231]

[0232] Note: S1 is the sum of the surface areas of the holes on the shell; S2 is the sum of the maximum cross-sectional areas of the finger-shaped holes in the core.

[0233] Table 2 (continued)

[0234]

[0235]

[0236] 1 It refers to the sum of the surface areas of the pores on the shell layer (S1) / the total surface area of ​​the shell layer × 100%.

[0237] Table 2 (continued)

[0238] Example PVC / wt% Polyacrylic acid / wt% Hydroxyl modified lithium ion sieve / wt% Example 1 19.2 3.9 76.9 Example 2 44 1.1 54.9 Example 3 34.5 8.5 57 Example 4 54.1 0.9 45 Example 5 66.64 0.06 33.3 Example 6 16.44 0.16 83.4 Example 7 19.3 3.8 76.9 Example 8 19.3 3.8 76.9 Example 9 19.3 3.8 76.9* Example 10 19.3 3.8 76.9 Embodiment 11 19.3 3.8 76.9 Comparative Example 1 20 0 80 Comparative Example 2 19.3 3.8 76.9 Comparative Example 3 19.3 3.8 76.9 Comparative Example 4 19.2 3.9** 76.9* Comparative Example 5 55.3 18.4 26.3*

[0239] * refers to the content of unmodified lithium ion sieve; ** refers to the content of polyacrylonitrile.

[0240] It can be seen from Table 2 that the lithium adsorption materials provided in Examples 1-11 of the present invention have a core with a specific pore structure and pores with a specific average diameter coated on the surface of the core, and the shell has a specific thickness. The lithium adsorption material with the above-mentioned specific structure presents a special structure with small pores in the outer shell and large pores in the inner core, which can increase the mass transfer rate of water. When it is used for lithium extraction in a liquid environment, it can significantly improve the adsorption capacity of lithium.

[0241] It can be seen from Table 1 that when the lithium ion sieve is modified by a hydroxyl-containing compound to obtain a hydroxyl-modified lithium ion sieve, the hydroxyl-modified lithium ion sieve is used to prepare a lithium adsorption material. Due to the increased compatibility, the lithium ion sieve in the prepared lithium adsorption material has better dispersibility and pore size distribution, thereby improving the adsorption capacity, water mass transfer rate and other properties of the lithium adsorption material when extracting lithium in a liquid environment.

[0242] Figure 1 is a surface SEM image of the lithium adsorption material of Example 1, Figure 2 This is a cross-sectional SEM image of the lithium adsorption material of Example 1. It can be seen that the pore size of the particle surface of Example 1 is uniform, and the pore size is about 0.5 μm. The cross section is finger-shaped pores, and the longest average length is 2.5 μm; the shortest average length is 1 μm. Figure 3 is a cross-sectional SEM electron microscope image of the lithium adsorption material of Example 1, Figure 3 It can be seen that the shell thickness of the particles of Example 1 is about 35.5 μm.

[0243] Although the lithium adsorption materials prepared in Comparative Examples 1-3 are also spherical and have an average particle size of 2-5 mm, the lithium adsorption materials prepared in Comparative Examples 1-3 do not have the specific pore structure defined in the present invention, and the shell pores and cross-sectional pores of the lithium adsorption materials are dense and few, resulting in a significant decrease in the porosity and BET of the lithium adsorption materials.

[0244] Figure 4 This is a SEM electron microscope image of the cross section of the lithium adsorption material of Comparative Example 1, Figure 5 This is a SEM electron microscope image of the cross section of the lithium adsorption material of Comparative Example 2. Figure 4 and Figure 5 It can be seen that the adsorption material powders prepared in Comparative Examples 1-2 are largely aggregated in the polymer skeleton, and in Table 2, the average particle diameter of the lithium ion sieve in the cross section of the lithium adsorption material prepared in Comparative Examples 1 and 2 is significantly increased.

[0245] The adsorption performance of the lithium adsorption materials obtained in the examples and comparative examples was tested, and the results are shown in Table 3.

[0246] Table 3

[0247]

[0248]

[0249] It can be seen from the results in Table 3 that compared with Comparative Examples 1-3, the lithium adsorption materials in Examples 1-11 of the present invention have a faster water mass transfer rate and a correspondingly larger adsorption capacity, and after being immersed in a high salt solution (lithium ion content 100 mg / L, magnesium ion concentration 20000 mg / L) for 48 hours, the volume change (volume expansion rate) is within 1%, indicating that the lithium adsorption material provided by the present invention has high resistance to swelling.

[0250] The lithium adsorption material of Example 1-11 was adsorbed under pH=9.5 and desorbed with 0.5M HCl. After 30 cycles, the solution was clear, indicating that the lithium ion sieve did not fall off the skeleton of the lithium adsorption material, and after 30 cycles, the adsorption capacity did not decrease significantly.

[0251] Furthermore, if Figure 6 As shown, by observing the SEM electron microscope picture of the cross-section of the lithium adsorption material of Example 1 after 30 cycles of use in the adsorption column (pH = 9.5 adsorption, 0.5M HCl desorption), it can be found that the lithium ion sieve powder in the lithium adsorption material is evenly dispersed, and the internal pores of the lithium adsorption material are free of salt crystals and cracks, indicating that the lithium adsorption material has excellent mechanical properties.

[0252] However, after the lithium adsorption materials of Comparative Examples 1 and 3 were used in adsorption and desorption cycles (pH=9.5 adsorption, 0.5M HCl desorption) for 30 times, the solution turned dark brown, lithium ion sieve powder leaked out of the solution, and the adsorption and desorption performance decreased significantly.

[0253] Furthermore, if Figure 7 As shown, by observing the SEM electron microscope picture of the cross section of the lithium adsorption material of Comparative Example 1 after 30 cycles of use in the adsorption column (pH=9.5 adsorption, 0.5M HCl desorption), it can be found that salt crystals and cracks exist in the pores inside the lithium adsorption material.

[0254] Figure 8is a photograph of the lithium ion adsorption material prepared in Example 1 of the present invention, Figure 8 It can be seen that the lithium ion adsorption material of the present invention is spherical or quasi-spherical.

[0257] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A lithium adsorption material, characterized in that: The lithium adsorption material comprises a core body and a shell layer coated on the surface of the core body; There are pores on the shell layer of the lithium adsorption material, and the average diameter of the pores measured by SEM electron microscopy is 0.01-2.5 μm; The core of the lithium adsorption material contains finger-shaped pores, and the longest average length of the finger-shaped pores measured by SEM electron microscopy on the cross section of the lithium adsorption material is 1-7 μm, and the shortest average length is 0.05-2.5 μm; The shortest average length of the finger-like holes in the core is greater than the average diameter of the holes in the shell; The thickness of the shell layer of the lithium adsorption material measured by SEM electron microscope is 1-550 μm.

2. The lithium adsorption material according to claim 1, wherein The average diameter of the pores in the shell of the lithium adsorption material measured by SEM electron microscopy is 0.1-0.5 μm; The longest average length of the pores of the cross section of the lithium adsorption material measured by SEM electron microscopy is 2-5 μm; the shortest average length is 0.5-1.5 μm; The thickness of the shell layer of the lithium adsorption material measured by SEM electron microscopy is 30-500 μm.

3. The lithium adsorption material according to claim 1 or 2, wherein The porosity of the lithium adsorption material is 60-80%, preferably 65-75%; Preferably, the lithium adsorption material is spherical and / or quasi-spherical; Preferably, the average particle size of the lithium adsorption material is 2-5 mm, preferably 3-4 mm; Preferably, the specific surface area of ​​the lithium adsorption material is 10-100m 2 / g, preferably 35-65m 2 / g.

4. The lithium adsorption material according to any one of claims 1 to 3, wherein The ratio of the sum of the surface areas S1 of the holes on the shell layer to the sum of the maximum cross-sectional areas S2 of the finger-shaped holes in the core body is 0.5-0.9:1, preferably 0.6-0.8:

1.

5. The lithium adsorption material according to any one of claims 1 to 4, wherein The lithium adsorption material includes a skeleton and a lithium ion sieve dispersed in the skeleton; The skeleton comprises polyvinyl chloride and polyacrylic acid; Preferably, the lithium ion sieve is a hydroxyl-modified lithium ion sieve, and the lithium ion sieve is connected to the framework via hydroxyl groups.

6. The lithium adsorption material according to claim 5, wherein Based on the total weight of the lithium adsorption material, the content of the polyvinyl chloride is 16-67wt%; the content of the polyacrylic acid is 0.06-9wt%; and the content of the lithium ion sieve is 45-85wt%; Preferably, based on the total weight of the lithium adsorption material, the content of the polyvinyl chloride is 16-54wt%; the content of the polyacrylic acid is 0.9-9wt%; and the content of the lithium ion sieve is 45-80wt%.

7. The lithium adsorption material according to claim 5 or 6, wherein The thickness of the coating layer formed by the compound providing hydroxyl groups in the hydroxyl-modified lithium ion sieve is 1-5 nm, preferably 3-5 nm; Preferably, the hydroxyl-modified lithium ion sieve is a polyphenol-modified lithium ion sieve; Preferably, the polyphenol is selected from at least one of tannic acid, tea polyphenol, apple polyphenol, grape polyphenol, eriodictyol, naringenin, epicatechin, luteolin, naringenin, kaempferol, myricetin and genistein; Preferably, the lithium ion sieve is selected from titanium-based lithium ion sieves and / or manganese-based ion sieves; Preferably, the lithium ion is selected from LiMn2O4, Li 1.6 Mn 1.6 O4、Li 1.33 Mn 1.67 O4、Li4Mn5O 12 、LiMnO2、Li2TiO3、Li 1.33 Ti 1.66 O4 and Li4Ti5O 12 At least one of; Preferably, the water content of the hydroxyl-modified lithium ion sieve is less than or equal to 0.5wt%, preferably 0.1-0.3wt%.

8. The lithium adsorption material according to any one of claims 5 to 7, wherein: The average particle diameter of the lithium ion sieve in the cross section of the lithium adsorption material measured by SEM electron microscope is less than or equal to 2.5 μm, preferably less than or equal to 1.5 μm.

9. The lithium adsorption material according to any one of claims 1 to 8, wherein Based on the total surface area of ​​the shell layer of the lithium adsorption material, the total area of ​​the pores on the shell layer is 30-90%, preferably 50-90%.

10. A method for preparing the lithium adsorption material according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: (1) mixing polyvinyl chloride, polyacrylic acid, lithium ion sieve and oil phase solvent to obtain a mixed solution; (2) Under the conditions of temperature of 20-60° C. and humidity of 40-80%, the mixed solution is added dropwise to an aqueous solvent to obtain a lithium adsorption material.

11. The method according to claim 10, wherein: In step (1), the lithium ions are screened from titanium-based lithium ion sieves and / or manganese-based ion sieves; Preferably, the lithium ion is selected from LiMn2O4, Li 1.6 Mn 1.6 O4、Li 1.33 Mn 1.67 O4、Li4Mn5O 12 、LiMnO2、Li2TiO3、Li 1.33 Ti 1.66 O4 and Li4Ti5O 12 At least one of; Preferably, the weight average molecular weight of the polyvinyl chloride is 50,000-110,000 g / mol; Preferably, the weight average molecular weight of the polyacrylic acid is 100,000-1.3 million g / mol; Preferably, the oil phase solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide; Preferably, the amounts of the polyvinyl chloride, the polyacrylic acid and the hydroxyl-modified lithium ion sieve are such that, based on the total weight of the lithium adsorbent material, the content of the polyvinyl chloride is 16-67wt%; the content of the polyacrylic acid is 0.06-9wt%; and the content of the lithium ion sieve is 45-85wt%; Preferably, based on the total weight of the lithium adsorption material, the content of the polyvinyl chloride is 16-54wt%; the content of the polyacrylic acid is 0.9-9wt%; and the content of the lithium ion sieve is 45-80wt%.

12. The method according to claim 10 or 11, wherein: In step (2), the mixed solution is added dropwise to the aqueous phase solvent at a temperature of 35-60° C. and a humidity of 60-80%; Preferably, the aqueous phase solvent is selected from at least one of water, ethanol and acetic acid, preferably water.

13. The method according to any one of claims 10 to 12, wherein: The lithium ion sieve is a hydroxyl-modified lithium ion sieve; Preferably, the lithium ion sieve is modified by using an aqueous solution containing a hydroxyl compound, and the hydroxyl-modified lithium ion sieve is obtained after solid-liquid separation and drying; Preferably, the hydroxyl-containing compound is a polyphenol; preferably at least one selected from tannic acid, tea polyphenols, apple polyphenols, grape polyphenols, eriodictyol, naringenin, epicatechin, luteolin, naringenin, kaempferol, myricetin and genistein; Preferably, the concentration of the aqueous solution containing the hydroxyl compound is 0.05 mg / L-0.1 mg / L; Preferably, the mass ratio of the lithium ion sieve to the hydroxyl-containing compound is 1:0.01-0.3; Preferably, the modification conditions include: reaction time of 30 min-4 h, reaction temperature of 25-40°C.

14. The method according to any one of claims 10 to 13, wherein: The method further comprises: a step of washing the lithium adsorption material with an acidic solution; Preferably, the lithium adsorption material is circulated and washed with an acidic solution under the action of a peristaltic pump; Preferably, the acidic solution is selected from at least one of hydrochloric acid, phosphoric acid and sulfuric acid; Preferably, H + Ion meter, the concentration of the acidic solution is 0.1-1 mol / L; Preferably, the flow rate of the peristaltic pump is 1-25 BV / h, and the cycle time is 1-48 h.

15. A lithium adsorption material obtained by the method according to any one of claims 10 to 14.

16. Use of the lithium adsorption material according to any one of claims 1 to 9 and 15 in lithium extraction, preferably in lithium extraction in a liquid environment.

Citation Information

Patent Citations

  • Preparation method of granular lithium adsorbent

    CN109225124A

  • Resin-based inorganic nanoparticle composite lithium extraction particle

    CN111905700A

  • Preparation method of porous spinning composite material and lithium extraction application thereof

    CN112619621A

  • PLGlu-SS-lithium ion sieve composite material and preparation method and application thereof

    CN115254052A

  • Lithium ion adsorption material as well as preparation method and application thereof

    CN116212830A